Mutaciones/ Proyecto Areguá: complexidades contextuais e tradições seletivas na prática de Marcos Benitez - Sanches, Douglas Colombelli Parra (2025)
This research aims to investigate and problematize the contextual complexities surrounding the practice Mutaciones: Provecto Areguá, an artistic production developed between 2004 and 2006 by Paraguayan visual artist Marcos Benitez. In this production, the artist employed the labor force and procedures of ceramic production from the city of Areguá, also incorporating various aspects of its products. The research is grounded in cultural studies frameworks, primarily based on the propositions of cultural theorist Raymond Williams, while engaging in dialogue with Néstor Garcia-Canclini, Jesús Martin-Barbero, and Tício Escobar to explore the contextual complexities and problematize aspects of this production. The research thus revealed the calculation undertaken in Mutaciones: Proyecto Areguá, in which the artist reflects on his Asunción-based references. These references, constituted by modernist artists who prescribed a “traditional popular Paraguayan ceramics,” represent an exclusionary formulation for Areguá’s ceramic production. Understanding this movement not only allowed for an understanding of the displacement of Areguá”s ceramic production in relation to the outlined tradition but also uncovered previously implicit elements, including subjects, procedures, conditions, and production relations that influenced Benitez’s practice. As a result, the investigation enables an understanding of Benitez’s practice in relation to modem trends of thought that were active in the actions of individuals and formations, which were predominant in the consolidation of art and cultural institutions during Paraguay’s redemocratization process.